Effect of the local charge disproportionation on the electronic structure of Ba Pb 1-x Bix03 - Sofo, Jorge O.; Aligia, Armando Ángel; Núñez Regueiro, M. D. (Comisión Nacional de Energía Atómica; Argentina, 1989)
Fil: Sofo, Jorge O. Comisión Nacional de Energía Atómica; Argentina